Optimalisasi Cara Bertindak dalam Pelaksanaan Patroli Satuan Sabhara Guna Mencegah Tindak Pidana Curanmor di Polres Karawang - Budi, Sakti Ferdinand Suryo (Advances in Police Science Research Journal, 2019)
The rise of motorcycle theft makes the police, especially the Karawang Regional Police area, must be able to provide a sense of security with the implementation of the Sabhara Unit Patrol to prevent criminal acts of Curanmor. Based on data from the Kerawang District Criminal Investigation Unit from 2017 to 2018, cases of deception have decreased in prostitution, but there is an imbalance in problem-solving. The purpose of this study is to find out how to act and steps in reducing the Criminal Acts of the Kerawang area. The method used in this study is a descriptive method which is expected to provide actual and detailed information and can describe the conditions, problems, and conditions of the Karawang area so that it can help in evaluating to determine designs and decisions in the future. This research refers to Article 28, paragraph (2). It has been regulated in Article 28 paragraph (1) of Kabaharkam Regulation No. 1 of 2017 dated February 16, 2017, which can be used as a reference in making Standard Operating Procedures made by the highest leadership, namely the Chief of Police. The results of this study are in the form of adjusting time, place, employees and coordination between the Polres and Polsek in conducting patrols. Then he took action against the residents' report and the suspect who was caught red-handed. Furthermore, in the form of a way of actions carried out by the Sabhara Police Unit of the Karawang Regional Police in minimizing criminal acts of fraud by looking at internal and external factors.